Digital currency and financial inclusion in Nigeria: lessons for development. Issue 1 (29th March 2022) - Ekong, Uduak Michael; Ekong, Christopher Nyong
Abstract : Purpose: This study aims to empirically investigate the effect of digital currency development (digital finance) on financial inclusion in Nigeria for the period. Nigeria undertook her digital currency development to rip the benefits of financial inclusion, safer remittances and exchange rate regularization among others. Design/methodology/approach: The researchers developed high-frequency quarterly data for the analysis from 2006:1 to 2020:4 in a weighted stepwise forward regression. A model similar to the one used by Demir et al. (2020) and Altunbas and Thornton (2019) with some modifications was developed. Findings: Findings suggest that (1) a unit rise in the usage of automated teller machines by citizens spontaneously raised financial inclusion in a quarter in Nigeria by 0.012 units and were statistically significant; (2) a percentage rise in the use of point of sales transaction by citizens in the country also raised financial inclusion in Nigeria by approximately 1%; (3) a percentage increase by mobile payment users in Nigeria will spontaneously increase financial inclusion by at least 0.4%; (4) a percentage rise in web payment services reduces financial inclusion by 22% in Nigeria; (5) Cumulative positive effect of digital finances on financial inclusion in Nigeria was approximately 7%. Practical implications: The researches show, using in-sample forecast, that while financial inclusion will grow in Nigeria, it will not be without systemic fluctuations. Based on the outcome, it is proposed that if the present digital currency penetration for the country is sustained at the present growth rate, the country may be more financially inclusive by 2% additionally by 2025 and 4% more by 2030. Originality/value: Originally, it is found that digital currency development are positive derivatives for financial inclusion in Nigeria. Cumulatively, the effect of digital finances on financial inclusion in Nigeria is approximately 7% positive.